Testicular tumours discovered during infertility workup are predominantly benign and could initially be managed by sparing surgery. Issue 4 (9th September 2018) - Lagabrielle, Samuel; Durand, Xavier; Droupy, Stéphane; Izard, Vincent; Marcelli, François; Huyghe, Eric; Ferriere, Jean‐Marie; Ferretti, Ludovic
Abstract: Background and Objectives: To evaluate the pathological features and recurrence of incidental testis tumours treated by partial orchiectomy in a population of infertile men. Methods: We retrospectively pooled, from four andrology referral centres, 32 patients diagnosed with testis mass during regular infertility workup. Patients included had an impaired sperm analysis and testis sparing surgery was performed to prevent secondary azoospermia or androgen therapy. Results: Mean age was 36 (IQR, 32 to 37). The mean largest tumoral diameter was 8.5 mm (IQR, 5 to 10). A total of 25% (8 of 32) of patients had a malignant tumour (seminoma, 7 of 32, 22%; teratoma, 1 of 32, 3%) and 75% (24 of 32) had a benign lesion (Leydig cell tumour, 23 of 32, 72%; scar tissue, 1 of 32, 3%). Malignant tumours were then managed by total orchiectomy (six of eight) or by radiotherapy (two of eight). With a mean follow up of 26 months (IQR, 8 to 32), one patient (3%) had an homolateral recurrence, which was a Leydig cell tumour. Not a single patient developed metastasis. Conclusion: Seventy‐five per cent of the tumours discovered during infertility management were of a benign pathology. A conservative approach could be proposed initially to avoid unnecessary orchiectomies. Orchiectomy and radiotherapy could be discussed as salvage therapies for malignant lesions.